ANTROPOLOGI SASTRA: KEBUDAYAAN YANG TERDOKUMENTASIKAN DALAM KARYA SASTRA - Salwa, Carissa; Maulana, Litha Syahfira; Pratiwi, Mita; Bahtiarudin, Muhamad; Julianto, Indra Rasyid (PT. CASA CENDEKIA MEDIA, 2025)
This research uses a literature study method with a qualitative descriptive approach, in which the sources analysed are selected based on their relevance to the topic under study. Anthropology is understood as a science that examines human behaviour and culture in various aspects of life. In literary studies, anthropology is one of the approaches that focuses on analysing the cultural elements contained in a literary work. Literary work itself is a medium of expression used to convey feelings, emotions, ideas, and thoughts of the author through writing. Therefore, literature can be considered as a reflection of the social and cultural reality of society in a certain period. Although the anthropological approach to literature is still relatively new, it allows us to understand the various cultural values contained in a literary work. Literary anthropology studies how the culture of a society is represented in literary texts, including the values, traditions, customs, and social changes that occur in a particular community. Through literary anthropological analysis, we can understand the relationship between literary works and their socio-cultural context. Literature is not only a means of entertainment, but also has an important role in documenting and preserving cultural heritage. Literary works often illustrate how a society views the world, both in terms of belief systems, norms, and patterns of social interaction. Based on the results of the literature study obtained, the anthropology contained in literary works reflects a culture and life in a particular society and generation. Thus, anthropological studies in literature help reveal the dynamics of culture that continue to develop in human life.